The efficacy of adding budesonide/formoterol to ipratropium plus theophylline in managing severe chronic obstructive pulmonary disease: an open-label, randomized study in China - Kewu Huang; Yanfei Guo; Jian Kang; Li An; Zeguang Zheng; Lijun Ma; Liping Peng; Hongyang Wang; Rong Su; Yohji Itoh; Chen Wang (Therapeutic Advances in Respiratory Disease, 2019)
Background: Patients diagnosed with chronic obstructive pulmonary disease (COPD) in China are commonly prescribed ipratropium plus theophylline (I+T) therapy. Studies have shown that an inhaled corticosteroid (ICS)/long-acting β 2 -agonist (LABA) combination is also efficacious in reducing symptoms and exacerbations. This study evaluated the efficacy and tolerability of adding budesonide/formoterol (BUD/FORM) to I+T in Chinese patients with severe COPD. Methods: A randomized, parallel-group, open-label, multicenter phase IV study (Clinical Trials.gov identifier: NCT01415518) was conducted in China. Patients received either BUD/FORM (160/4.5 µg; two inhalations twice daily [bid] via Turbuhaler ® ) + I (20 µg per inhalation, two inhalations four times daily) + T (100 mg bid) or I+T alone for 12 weeks. The primary efficacy variable was change from baseline in predose forced expiratory volume in 1 s (FEV 1 ). Results: A total of 584 patients were randomized equally between treatment groups. At the end of the study, the BUD/FORM plus I+T group displayed significant improvements in predose FEV 1 versus the I+T group (between-group difference 6.9%; 95% confidence interval [CI]: 4.3, 9.6; p < 0.0001). Forced vital capacity, inspiratory capacity, peak expiratory flow and health-related quality of life (HRQoL) scores were significantly improved (all p  < 0.0001) and exacerbation frequency was reduced (43.5% reduction; rate ratio 0.565, 95% CI 0.325, 0.981; p  = 0.0425) with BUD/FORM plus I+T versus I+T alone. Conclusion: Patients with severe COPD in China treated with BUD/FORM plus I+T showed significant improvements in lung function and HRQoL and a reduction in exacerbations compared with I+T alone. Both treatments were well tolerated and no safety concerns were noted. The reviews of this paper are available via the supplemental material section .